Effective Digital Business Management Strategy: A Structured Approach to Turning Challenges into Opportunities for Sustainable Growth and Innovation - Rasyad, Rizky Zakariyya; Nuraini Mawardah, Putri (International Journal of Management Science and Information Technology, 2024)
Digital transformation has become one of the main pillars of modern business strategy, requiring companies to adapt to technological developments and maximize emerging opportunities. This article explores effective digital business management strategies, focusing on a structured approach to transform challenges into opportunities for growth and sustainable innovation. Through a qualitative approach based on literature studies and case analysis, this study identifies key elements in digital business management strategies, including the use of information technology (IT) and management information systems (MIS), the use of data and analytics, organizational flexibility, continuous innovation, and strategic collaboration with external parties. The results show that companies that successfully implement this strategy can adapt quickly to market changes, improve operational efficiency, and create competitive advantages. Flexibility and continuous innovation are also found to be important factors in ensuring business continuity amidst technological disruption. In addition, collaboration between companies, startups, and academic institutions is a key element in driving innovation and optimizing resources. This article contributes to the academic literature and business practice, by offering practical guidance for companies to formulate superior digital strategies in the era of global competition.